2018
DOI: 10.1021/jacs.8b07050
|View full text |Cite
|
Sign up to set email alerts
|

Zigzag Ligands for Transversal Design in Reticular Chemistry: Unveiling New Structural Opportunities for Metal–Organic Frameworks

Abstract: Herein we describe the topological influence of zigzag ligands in the assembly of Zr(IV) metal-organic frameworks (MOFs). Through a transversal design strategy using reticular chemistry, we were able to synthesize a family of isoreticular Zr(IV)-based MOFs exhibiting the bcu-rather than the fcu-topology. Our findings underscore the value of the transversal parameter in organic ligands for dictating MOF architectures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 64 publications
(36 reference statements)
3
72
0
2
Order By: Relevance
“…Besides, a series of zigzag ligands have also been introduced into bcu Zr-MOFs. [181] In addition, ditopic linkers with different sizes and functional groups can be used to construct bcu Zr-MOFs. [182][183][184][185] Different structures can be obtained using ditopic V-shaped ligands.…”
Section: Zr-mofs Based On Ditopic Linkersmentioning
confidence: 99%
“…Besides, a series of zigzag ligands have also been introduced into bcu Zr-MOFs. [181] In addition, ditopic linkers with different sizes and functional groups can be used to construct bcu Zr-MOFs. [182][183][184][185] Different structures can be obtained using ditopic V-shaped ligands.…”
Section: Zr-mofs Based On Ditopic Linkersmentioning
confidence: 99%
“…[91][92][93] However, before the advent of transversal reticular chemistry, no clear focus had been made on the potential of their unique shape ( Figure 6a). 50 By adding the transversal parameter of width (w) to the height (h) of the ligands, Guillerm et al demonstrated that, along with making ligands taller or shorter, they could also stretch them transversally, thus breaking the collinearity of the binding carboxylates. In the case of Zr-based MOFs, this effect is reflected by generation of geometry mismatch ( Figure 6b), as zigzag ligands do not match the perfect alignment of Zr clusters.…”
Section: Zigzag Ligands: Transversal Reticular Chemistrymentioning
confidence: 99%
“…32 Along these lines, scientists can employ less-symmetric organic ligands, with bend-angles, 34 introduce steric hindrance 49 or use zigzag-shaped ligands (transversal reticular chemistry). 50 These strategies all induce structural irregularity known as geometry mismatch.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the combination of hexanuclear MBBs with tetratopic ligands may result in an excess of 10 unique nets depending on node connectivity and various conformational properties . Where such parameters may be systematically controlled, the practice of isoreticular chemistry allows further opportunities to tune material properties such as the defects concentration, as seen in a recent example illustrating the use of transversal design in Zr‐MOFs by Guillerm et al Nevertheless, the synthetic effort involved in precise manipulation of these parameters may be significant, yet conflict with other attempts to introduce nonstructural functional moieties.…”
Section: Reticular Chemistry Of Mofsmentioning
confidence: 99%